Seasonal patterns of aflatoxin M1 contamination in commercial pasteurised milk from different areas in Thailand - Suriyasathaporn W. (2014)
Aflatoxin M 1 (AFM 1) levels were determined in pasteurised milk from five commercial trademarks produced in different areas in Thailand. One hundred and twenty milk samples were collected from local markets in Chiang Mai province, Thailand, to evaluate AFM 1 concentrations using immunoaffinity columns and high-performance liquid chromatography with fluorescence detection. The overall median AFM 1 level was 0.023 μg L -1 ranging from 0.004 to 0.293 μg L -1. All trademarks had average AFM 1 concentrations lower than 0.05 μg L -1, with those in Trademarks 3 to 5 being higher than Trademarks 1 and 2 (P < 0.01). All trademarks had different seasonal patterns of AFM 1, even though operating in the same area. However, only Trademark 3 showed significant differences of AFM 1 levels between seasons. The results suggested that farm management factors, rather than environment factors, were likely to be the main cause of AFM 1 contamination in dairy products. © 2012 Taylor and Francis Group, LLC.